Productivity Growth in Germany: No Sustainable Economic Recovery in Sight - Georg Erber; Ulrich Fritsche (Weekly Report, 2009)
By international comparison the productivity development of the overall economy in Germany has taken a serious hit after the reunification boom. Since then Germany has fallen behind not only in comparison to the USA and emerging-market nations like South Korea, but also in comparison to other EU countries. However, the economic upswing in 2006 led to a temporary increase in hourly productivity of labor per employed person. Can this increase be interpreted as a return to a higher trend growth? Econometric tests indicate that it probably primarily concerns a cyclically induced increase. Thus the decline of the medium-term growth rate came at best to a standstill. If the productivity growth should improve on a sustained basis, then a growth-orientated economic policy is required.
Keywords: C22; C32; E23; E24; E30; E37; 330; Productivity growth; Time series; decomposition; Business cycle; Long-term trend